Board characteristics and cost of debt: Evidence from Indonesia - Stefany, Stefany; Joni, Joni (Jurnal Manajemen Maranatha, 2020)
Corporate governance has been an important issue for investors, practitioners, and regulators. This is because board characteristic as central feature of corporate governance has a significant impact on the economy and the firm’s operation. This study investigates the effect of board characteristics on cost of debt for the Indonesian listed companies for the period 2016-2017. The final sample of this study is 777 firm-year observations. We use multiple regressions for the main analysis and Generalized Method of Moments (GMM) to test for endogeneity. The results show that board size is negatively significantly associated with the cost of debt, yet female board and independent boards are not related to cost of debt. The results are still consistent after testing for endogeneity issue.